Science Teaching at Primary Level based on BEME Methodology - Cisneros-Chávez, Betsy Carol; Alejandro-Oviedo, Olga Melina; Villalba-Condori, Klinge (International Journal of Psychosocial Rehabilitation, 2019)
The main objective of this work was to measure the intervention of a methodological proposal of science teaching focused on the primary education level, which has four phases: information search, experimentation, measurement of results and scientific explanation. The intervention was adapted to the Flow Theory, during 8 months in 15 educational institutions with 343 students. The results obtained in comparison to before and after the intervention in the learning of the area of Science and Technology is 3.85 points for the median, considering the whole universe; likewise, there are favorable effects in the behavior of the learning, achievement of competencies and emphasis on the sense of homogeneity with respect to the achievement of the purpose of learning; 9 of the 15 institutions decreased the variance in the after and the parametric behavior was maintained; the other 6 go from nonparametric to parametric behavior, a result that provides a very important element in the learning of the curricular area, since BEME favors even more the cognitive deepening favoring above all the situational challenges that correspond to the experiences made with the BEME Scientific lunchboxes